Swine flu: A threat to human health - Syeda Samra Iqbal Jafri; Muhammad Ilyas; Muhammad Idrees (African Journal of Pig Farming, 2013)
Influenza virus has caused major global epidemics since 1918. Although this commonly circulating viral strain is not virulent enough to cause mortality, but the re-assortment of viral genome to mutate at a very high rate can lead to the emergence of a highly virulent strain that may lead to next pandemics. Swine flu is an example of re-assortment of two viruses in pig causing thousands of deaths in the whole world especially in the United States of America by zoonotic jumps. This review addresses the biological and epidemiological aspects of swine flu virus and efforts to have a control on the virus globally